Development of building energy conservation standards for Beijing - Yu Hong; Surapong Chiraratananon; Karmazsin, Etienne; Giap Van Dang; The Government of France (Bangkok : Asian Institute of Technology, 1994)
This study deals with development of Building Energy Conservation Standard in Beijing by focuses on building envelope. The overview of existing buildings (including tourist hotels and residential buildings) and Building Energy Conservation Standards in China and Beijing at present has been done in this study. 14 type walls, 7 type roofs and 6 type windows which normally used and recommended in Beijing were used for analysis and calculation. For calculation of effective solar radiation (RDPR), solar factor (SF), equivalent temperature difference (TDeq) and heat flux through walls, roofs and windows, some program write in turbo-basic were used. Hourly meteorological data of the year 1984 in Beijing was used also for the calculation. The relations between heat flux with thermal resistance of building envelope, window wall ratio, building's orientation, air ventilation and infiltration, and daylighting were analyzed by using the calculation results. The analysis of energy consumption Vs daylighting was also done by calculation. Two case with different purpose of use (office and residential buildings) were considered in the study. The concept of OTTV, which popular used in US and South East Asia but have not been used in China, was considered in this study. Finally, the costs of energy efficient measures for building envelope was calculated by taking one example building.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1994
Keywords: Buildings -- China -- Beijing -- Energy conservation